Ekoteologi dalam Menyikapi Krisis Ekologi di Indonesia Perspektif Seyyed Hossein Nasr - Wasil Wasil; Muizudin Muizudin (Refleksi, 2023)
This library research descriptively explains the causes of the ecological crisis in Indonesia by using the ecotheological approach in the construction of Seyyed Hossein Nasr’s thought. This research shows that the ecological crisis is correlated with a perspective that is not in favor of nature (anthrophocentrism), modern humans lose their existence-spiritual and understanding of nature that is desacralized. Ecotheology is then used as a strategic basis for solving the ecological crisis in the midst of Indonesian religious society by mainstreaming ecotheology through religious leaders, pesantren, educational institutions, and NGOs.